Under Pressure? The Link Between Mandatory Climate Reporting and Firms' Carbon Performance. (March 2023) - Bauckloh, Tobias; Klein, Christian; Pioch, Thomas; Schiemann, Frank
We examine whether and how mandatory climate reporting leads to changes in firms' carbon emissions. Drawing on legitimacy theory and using a difference-in-differences design, we assess the effect of the Greenhouse Gas Reporting Program (GHGRP), introduced by the Environmental Protection Agency (EPA) in 2010, on the carbon performance defined as carbon intensity and absolute carbon emissions of affected firms. We find that firms affected by the GHGRP improve their carbon intensity significantly more than unaffected firms after the introduction of the GHGRP, but not their absolute carbon emissions. The results are robust to changes in the difference-in-differences design. Overall, our study contributes to research on mandatory climate reporting by assessing the GHGRP's suitability to generate a real sustainable change in firms' operations and reduce their negative impact on our climate.